1998
DOI: 10.1172/jci973
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of platelet aggregation as a consequence of different shearing flow conditions.

Abstract: Platelet aggregation contributes to arresting bleeding at wound sites, but may cause occlusion of atherosclerotic vessels, thus curtailing blood flow to vital organs. According to current dogma, the integrin alphaIIbbeta3 plays an exclusive role in linking platelets to one another through interactions with fibrinogen or vWf. We demonstrate here that, depending on shearing flow conditions, this process may require vWf binding to glycoprotein Ibalpha, even when alphaIIbbeta3 is competent to bind adhesive ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
204
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(218 citation statements)
references
References 39 publications
10
204
1
3
Order By: Relevance
“…31 Conditions of high and low shear may thus occur in close proximity to thrombotic deposits, and the sudden change from low to high shear around the growing thrombus may take place synergistically by reinforcing the binding to activated GPIIb/IIIa. 25 Although we observed a significant correlation between the plasma level of vWF or the amount of larger vWF multimers and the extent of high shear-induced SIPA, a direct relationship may not exist between these parameters. Rather, the elevation in plasma vWF and/or the extent of larger multimers may be a consequence of the onset of ACSs.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…31 Conditions of high and low shear may thus occur in close proximity to thrombotic deposits, and the sudden change from low to high shear around the growing thrombus may take place synergistically by reinforcing the binding to activated GPIIb/IIIa. 25 Although we observed a significant correlation between the plasma level of vWF or the amount of larger vWF multimers and the extent of high shear-induced SIPA, a direct relationship may not exist between these parameters. Rather, the elevation in plasma vWF and/or the extent of larger multimers may be a consequence of the onset of ACSs.…”
Section: Discussioncontrasting
confidence: 62%
“…2,23,24 Recent data indicate that plasma vWF and platelet GPIb are essential in the response to varying hemodynamic conditions and that vWF-dependent platelet aggregation mediated by the vWF-GPIb interaction is necessary to functionally complement the activated GPIIb/IIIa in the presence of elevated fluid dynamic forces. 25 In contrast, it has been shown that high shear-induced aggregation of washed platelets increases as a function of the concentration of exogenous purified vWF. 26 In addition, because wall shear rates of 3000 to 10 000 s Ϫ1 have been measured at the top of plaques, causing a 50% occlusion of the coronary arteries, 27 vWFGPIb binding may lead to arterial occlusion in a patient with atherosclerosis and precipitate a disease such as an ACS.…”
Section: Discussionmentioning
confidence: 98%
“…Injury to a blood vessel wall causes exposure to the blood of molecules embedded in the wall, including collagen and tissue factor. Blood platelets adhere to the collagen and become activated, thus beginning the process of platelet aggregation (Ruggeri 1994;Goto, Ikeda, Saldívar, and Ruggeri 1998). Tissue factor initiates the coagulation process which involves a tightly regulated network of enzyme reactions (Jesty and Nemerson 1995;Mann, Nesheim, Church, Haley, and Krishnaswamy 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The two principle adhesive ligands promoting platelet aggregation are von Willebrand factor (vWf) 1 and fibrinogen, with each having distinct, complementary roles in this process (1)(2)(3)(4)(5). Fibrinogen acts as a bridging molecule between adjacent activated platelets and is the principle adhesive ligand promoting platelet aggregation under low and intermediate shear flow conditions (1,2).…”
mentioning
confidence: 99%